Conversion of Residual Biomass into Valuable Biofuels by Co-Hydrothermal Carbonization for Utilization in Household Pellet Stoves - Santander-Moya, R; Cubillos-Montecino, F; Diaz-Robles, L; Murillo-Romero, H (Elsevier Ltd, 2021)
The co-hydrothermal carbonization of rapeseed meal (RM) and pine sawdust (PS) was optimized to obtain biofuels to be used in household pellet stoves. The methodology of optimization of multiple responses was applied on two sets of responses: mass yield-higher heating value-ash content (MY-HHV-AC) and energy yield-ash content (EY-AC) as a function of the RM fraction (%RM) and the reaction temperature (RT). The optimal conditions were 34.5% of RM and 209.3 °C of the MY-HHV-AC set, whereas 30.0% of RM and 193.4 °C were the EY-AC set s optimal parameters. After validation of the optimal responses, the resulting hydrochars were then pelletized before burning. Gaseous and particulate emissions were measured from the combustion of optimal hydrochars and their corresponding untreated biomasses in a commercial pellet stove. The most outstanding findings from hydrochar pellets were associated with decreased emissions of incomplete combustion such as CO and particulate matter, especially by the EY-AC hydrochar, which showed a significantly lower particulate emission than the local emission limit. Based on these results, this work reflects a promising application of hydrothermal carbonization on power generation and the prospective introduction of hydrochar pellets in the global market. © 2021 Elsevier Ltd
Keywords: Hydrothermal carbonization; Waste management; Hydrochar pellets; Hydrochar combustion; Pellet stove; Particulate matter